Existence of Fixed Points for a Class of Decreasing Operators with Parameter and Applications - Xingchang Li; Shiqin Tian (Journal of Mathematics)
This paper studies the existence of fixed points for a class of decreasing operators with parameter in real Banach spaces. The existence theorems of fixed point are obtained as when the parameter is increasing, there will still be a large fixed point. These results have reduced the requirements of convexity, compactness, and lattice structure of spaces. By this new method, the existence of solutions for a class of second-order differential equations with parameter in infinite intervals is studied.